PENGARUH UKURAN PERUSAHAAN, FINANCIAL LEVERAGE DAN STRUKTUR KEPEMILIKAN TERHADAP PERATAAN LABA (INCOME SMOOTHING) (STUDI PADA PERUSAHAAN BADAN USAHA MILIK NEGARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020) - Tiwow, Santi; Tinangon, Jantje J.; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to examine and find empirical evidence that firm size, financial leverage and ownership structure affect income smoothing. This research was conducted by a State-Owned Enterprise (BUMN) listed on the Indonesian Stock Exchange (IDX) for the 2016-2020 period. The research method used is a quantitative research method with an associative approach. The data in this study is secondary data in the form of annual reports of state-owned companies. The sample in this study were 15 state-owned companies. The data analysis tool used in this study is logistic regression analysis, with the help of SPSS 22 software. The results show that company size, financial leverage and ownership structure have no effect on income smoothing